2009
DOI: 10.2174/187221509789318405
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Essential Amino Acids and Health Benefit Components in Grain Crops for Improved Nutritional Values

Abstract: Improving essential amino acids or protein content, along with other phytonutrients in the food crops, will affect a great portion of the world population, especially in developing countries where rice grain is the main source of protein. Malnutrition, including deficiencies in protein/energy, iron/zinc, vitamin A, and iodine, causes a total 24,000 deaths per day worldwide. The problem is severe where rice is the major staple food. Protein deficiency involves both the quantity (amount) and quality (the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Lysine is considered the most important essential amino acid, and due to it is not synthesized in animals it must be acquired through diet. There is great interest in increasing the content of lysine in cereal crops since it has both an economical and humanitarian importance, especially in developing countries where the diet is mainly composed by a single cereal [53], [54]. Mutant high-Lys lines have been obtained in maize opaque-2 mutants [55] and opaque-2 -derived quality protein maize (QPM) lines [56], [57].…”
Section: Resultsmentioning
confidence: 99%
“…Lysine is considered the most important essential amino acid, and due to it is not synthesized in animals it must be acquired through diet. There is great interest in increasing the content of lysine in cereal crops since it has both an economical and humanitarian importance, especially in developing countries where the diet is mainly composed by a single cereal [53], [54]. Mutant high-Lys lines have been obtained in maize opaque-2 mutants [55] and opaque-2 -derived quality protein maize (QPM) lines [56], [57].…”
Section: Resultsmentioning
confidence: 99%
“…The researchers have tested four different strategies as described below: 1 Expressing recombinant genes encoding synthetic proteins with higher proportions of Met and/or Lys. Although significant efforts were invested in designing synthetic genes encoding proteins rich in Met and/or Lys, this strategy faced major difficulties associated with protein stability, digestibility and toxicity (for review, see Beauregard and Hefford, 2006;Wenefrida et al, 2009). 2 Expressing recombinant genes encoding seed storage proteins fortified with additional codons for these two essential amino acids.…”
Section: Enhancement Of Lys and Met Contents By Expressing Genes Encomentioning
confidence: 99%
“…Forsyth et al, (Forsyth et al, 2005) and Torrent et al, (Torrent et al, 1997) reported that the barley chymotrypsin inhibitor 2 as well as maize c-zein that were modified to have higher number of Lys codons stably accumulated in maize cells. Likewise, expression in rice seeds of a chimeric gene containing combined sequences of a rice glutelin and a Lys-rich protein from winged bean led to the elevation of total Lys level by more than 45%, compared with the control nontransformed genotype (Wenefrida et al, 2009). Several other modified proteins were also tested to increase the Met content in plants.…”
Section: Enhancement Of Lys and Met Contents By Expressing Genes Encomentioning
confidence: 99%
See 1 more Smart Citation
“…Some foods do contain anticancer compounds. Phytonutrients, often found in pungent and bitter vegetables, include resveratrol in grapes and curcumin in turmeric (Azari et al 2009, Feeney 2004, Greenlee, Hershman and Jacobson 2009, Holst and Williamson 2008, Kale, Gawande and Kotwal 2008, Kaur, Agarwal and Agarwal 2009, Lanzotti 2006, Mates et al 2011, Mattoo et al 2010, McGrath and Spigelman 2008, Neto 2007, Surh 2008, Wahlqvist and Lee 2007, Wenefrida et al 2009). Other molecules, including sulforaphane and genistein, an isoflavone found in soybeans, are currently being tested as pharmaceutical agents in cancer prevention (Ali et al 2005, Caetano et al 2006, Takahashi et al 2006, Shenouda et al 2004.…”
Section: Dietmentioning
confidence: 99%